Survey of patients with cystic fibrosis and caregivers decisions regarding CFTR modulators. Issue 11 (3rd July 2020) - George, Ashish; Smith, Beth; Sawicki, Gregory S.; Goetz, Danielle M.
Abstract: Cystic fibrosis transmembrane conductance regulator (CFTR) modulators are a novel approach to CF management that has become more readily available chronic CF therapies for certain populations of patients with CF. A cross‐sectional survey of adults with CF and caregivers of pediatric patients with CF was done in two CF Centers to better understand the decision‐making process including the potential influence of social media, CF care‐teams, and family members on their decision whether to begin a CFTR modulator. For the 90 participants, the most common influences in the decision to start modulator therapy were the CF providers/care teams (n = 63), parents (n = 49), and individuals with CF (n = 27). The most impactful influence in the decision‐making process were providers/care team (n = 47) and parents (n = 18). Social media was an influence for only 12 respondents, with an overall positive impact. Information from the CF Foundation was an influence for 12 participants and the main influence for six participants. The most common reasons for stopping lumacaftor‐ivacaftor were having tezacaftor‐ivacaftor as an option (n = 25) and side‐effects (n = 15). Family and CF clinicians were the two main influences on the decision to initiate modulator therapy. CF clinicians were seen to be the most influential source. Social media had less influence on the decision‐making process than expected despite the wide presence of the CF community online.